MANAGEMENT BY DIGITAL RESPONSIBILITY IN HEALTH ORGANIZATIONS - Meier, Jutta Juliane; Weigand, Christian; Bauer, Jochen; Eskofier, Björn (Proceedings of the International Conferences on Big Data Analytics, Data Mining and Computational Intelligence 2024, BigDaCI 2024; Connected Smart Cities 2024, CSC 2024; and e-Health 2024, EH 2024, 2024)
This paper describes the Digital Responsibility Goals, their purpose, and their exemplary relevance for digital innovations in the health sector. In addition, the document makes a first proposal for implementing digital responsibility through a management system based on the Digital Responsibility Goals.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Digital Health; Digital Responsibility; Digital Sovereignty; European Digital Rights; Framework; ISMS; Management Approaches; Patient Participation; Principles; Responsible AI; Trust